Identifikasi Miskonsepsi Menggunakan Four-Tier Diagnostic Test Pada Materi Kalor Kelas VII SMP Negeri 13 Medan - Ndruru, Fatty Kurnawati; Pardede, Hebron; SItinjak, Erni Kusrini (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the level of students' misconceptions on the material of heat using a four-tier test. This type of research is descriptive quantitative research. The subjects of this study were students of class VII 2 SMP Negeri 13 Medan totaling 60 people. The data collection instrument used in this study was a question in the form of a four-tier multiple choice test (Four-Tier Diagnostic Test) and 2 option reasons for respondents. Data processing in this study used the interpretation of the Four-Tier Diagnostic Test results in Table 3.6. The results showed that there were misconceptions that occurred in class VII 2 students as evidenced by the average percentage of the results obtained, namely, students who experienced Understanding Concepts (PK) as much as 20.0%, students who experienced Error (E) as much as 6.3%, students who experienced Not Understanding Concepts (TPK) as much as 20.7% and students who experienced Misconception (M) as much as 45.3%. While the level of misconceptions that occur in class VII 3 students is evidenced by the average percentage of results obtained, namely, students who experience Concept Understanding (PK) as much as 26.2%, students who experience Error (E) as much as 7.8%, students who experience Not Understanding the Concept (TPK) as much as 22.2% and students who experience Misconception (M) as much as 48.2%. Based on this research, it can be concluded that the Four-Tier Diagnostic Test can identify misconceptions that occur in students.